O professor orientador de informática educativa: o curador de TDIC na Rede Pública Municipal de Educação de São Paulo - Costa, Rosana Magnani da (2019)
This paper is inserted in the line of research new technologies in education of the Graduate Program in Education: curriculum of PUC SP. It proposes to study the actions of the teacher instructor of educational informatics in what refers to the choices that makes of digital educational resources in the pedagogical practice, seeking to approach this activity to the actions of an educational curator. The methodology of the research has a qualitative approach and employs the documentary analysis of publications of the Municipal Department of Education of São Paulo that guide the actions of the Instructional Teacher of Educational Informatics and the analysis of the answers of a group of teachers to a questionnaire, seeking to know and identify the performance of this professional in the curation of digital educational resources. Some categories of analysis have been presented that relate to the alignment of educational resources to the curriculum, such as: content quality; the facilitation of the learner's learning experience and the reputation of the author and institution producing digital resources. The data point to the role of the POIE as curator of digital resources, even though the official documents did not include training processes or theoretical contents that guided the actions of the curator and curation. It was identified that the curing action performed by the POIE focuses on the facilitation aspect of the students' learning experience. This research suggests a roadmap for the analysis of digital educational resources, focusing on the criteria: ease of use; student engagement; pedagogical foundation; teacher orientation; content; state of the art and adequacy of contents